UPAYA BIGHIT ENTERTAINMENT DALAM MENDUKUNG DIPLOMASI BUDAYA KOREA SELATAN DI PASAR MUSIK AMERIKA SERIKAT - Annisa Kusumastuti Subiakto (2021)
The integration of information and communication technology that occurs as a result of the globalization process provides an opportunity for a country's culture to become part of a country's public diplomacy. South Korea uses cultural diplomacy to build a positive image for its country and achieve its national interests, namely to increase the positive image of its country in the eyes of foreign audiences. The South Korean government provides various forms of support for their cultural industry to be able to enter overseas markets. However, it turns out that the cultural diplomacy carried out by South Korea has experienced various challenges in the United States music market, one of which is the perception that South Korean musicians commit plagiarism over American popular music. This study aims to determine the cultural diplomacy efforts undertaken by BigHit Entertainment, as one of the South Korean music agency companies in the United States music market. Researchers used cultural diplomacy theory to analyze cultural diplomacy efforts carried out by BigHit Entertainment through the principles of cultural diplomacy and the concept of national interest to find out whether the cultural diplomacy carried out by BigHit Entertainment can help the South Korean government achieve its national interests. The use of qualitative research methods with a case study approach was chosen by researchers to describe the Korean Wave phenomenon as a form of cultural diplomacy carried out by the South Korean government and the efforts made by BigHit Entertainment to support this cultural diplomacy. The results of this study indicate that the cultural diplomacy efforts carried out by BigHit Entertainment have a positive influence on the cultural diplomacy efforts of the South Korean government in the US music market to increase the positive image of the country in foreign audiences and support the South Korean government to achieve its national interests in several other sectors such as sector, economy, and politics.